Ember-safe attic and roof vents. (Architectural Record, 2008)
The article profiles a series of roof vent products which are manufactured by Brandguard Vents of San Clemente, California. A discussion of the features of the vents, which have been designed to meet fire codes in California which require that all exterior vents be designed to resist fire ember intrusion, is presented.